Understanding the drivers of fleet emission reduction activities of the German car manufacturers - Mazur,CM; Brandon; Offer; Contestabile (Environmental Innovation and Societal Transitions, 2015)
The current mobility system, dominated by fossil fuel poweredautomobiles, is under increasing pressure due to its environmentalimpact. To address this issue there is a need for a transitionof the system towards one that is more sustainable, including theintroduction of car technologies that allow a decrease in fuel consumptionand the substitution of fossil fuels as primary energysource. Due to the stability of the current automotive industryand the dominance of the internal combustion engine technology,it is expected that the incumbent firms and their activities willplay a crucial role in the transition. Policy makers have thereforeintroduced a variety of policies to encourage the industry to providesuitable solutions.We have conducted amicro-level analysis of howthe threemain German carmanufacturers have changed their activitiesin the field of low emission vehicle technologies in response tonational/international events and policy making. Our analysis suggeststhat policy makers only have limited influence on the typeof disruptive solution that is chosen by these individual companiesand that activities related to solutions that were not familiar to theindividual car manufacturer were mainly induced by internal or external champions. Still, while the existence of regulatory policiesallowed such activities to succeed, on its own it only encouraged theindustry to work on incremental solutions based upon the knowledgealready possessed.